Analisis Kualitas Pelayanan Publik di Kantor Urusan Agama (KUA) Kecamatan Jebres, Kota Surakarta dengan Menggunakan Diagram Kartesius - Aji Putri, Masykurotur Rizqi; Al-Azkiya, Muhammad Emir; Fazira, Arni; Orpa Dimara, Yemima Inanse; Setyowati, Kristina (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2025)
This study aims to analyze the quality of public services at the Jebres Subdistrict Religious Affairs Office (KUA) using a Cartesian diagram. This study uses a quantitative method with a survey approach. The data for this study were collected through the distributions of questionnaires at the KUA Jebres Subdistrict. The findings of this study show that there are five criteria that fall into quadrant A (need to be improved) in the Cartesian diagram, such as timeliness of service and employee problem-solving ability. Several criteria that fall into quadrants C and D, such as accessibility and employee appearance, are considered less important by the public, so they do not affect the overall performance of the KUA Jebres Subdistrict. Meanwhile, several criteria, such as the speed of the service process and the suitability of procedures, fall into quadrant B, which shows good performance and has met public expectations. In general, the quality of public services at the KUA Jebres Subdistrict is quite good, but there are several criteria that need to be improved, which are listed in quadrant A to ensure that the quality of services provided can meet public expectations. Keywords: Quality of Services, Cartesian Diagram, KUA Jebres Subdistrict, Surakarta